Tutorials as a flexible alternative to GUIs: An example for advanced model calibration using Pilot Points. (April 2015) - Moeck, Christian; Hunkeler, Daniel; Brunner, Philip
Abstract: Environmental modelling software with graphical user interfaces (GUIs) are user friendly and help to focus on the aspects of modelling rather than on the technicality of the underlying code. This is a fundamental advantage compared to codes without a GUI, as the absence of a GUI can prohibit the widespread application of a software tool. However, there is a downside to GUIs, too. They commonly lag behind the newest software development. We argue that tutorials are a flexible but undervalued alternative to GUIs, and are convinced that tutorials can help to make complex software accessible to an increased number of users. As an example to demonstrate our point, we have written a tutorial that illustrates the use of Pilot-Point based calibration made available through PEST in the HydroGeoSphere modelling environment. We hope that this example will encourage the modelling community to develop tutorials and make them available to the wider public. Highlights: Workflow and tutorial are provided for employing the Pilot Points method without a GUI. We demonstrate the application of Pilot Points calibration with HydroGeoSphere We compare methods to identify dependence of estimated parameters on observations.